2007
DOI: 10.1103/physrevb.76.014410
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale suppression of magnetization at atomically assembled manganite interfaces: XMCD and XRMS measurements

Abstract: Using polarized X-rays, we compare the electronic and magnetic properties of a La 2/3 Sr 1/3 MnO3(LSMO)/SrTiO3(STO) and a modified LSMO/LaMnO3(LMO)/STO interface. Using the technique of X-ray resonant magnetic scattering (XRMS), we can probe the interfaces of complicated layered structures and quantitatively model depth-dependent magnetic profiles as a function of distance from the interface. Comparisons of the average electronic and magnetic properties at the interface are made independently using X-ray absor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 26 publications
7
48
2
Order By: Relevance
“…Figure 3(a) shows x-ray magnetic circular dichroism (XMCD) spectra at the Mn and Ti L edge of ½LSMO 6 =STO 2 8 at 6 K in a 1 T magnetic field, conducted at the ID08 Beamline of the European Synchrotron Radiation Facility. The Mn XMCD signal of 27% is consistent with previous studies on LSMO/STO interfaces [22]. Remarkably, a clear dichroic signal is also observed at the Ti edge demonstrating the ferromagnetic character of STO, although bulk STO is a diamagnetic band insulator.…”
supporting
confidence: 78%
“…Figure 3(a) shows x-ray magnetic circular dichroism (XMCD) spectra at the Mn and Ti L edge of ½LSMO 6 =STO 2 8 at 6 K in a 1 T magnetic field, conducted at the ID08 Beamline of the European Synchrotron Radiation Facility. The Mn XMCD signal of 27% is consistent with previous studies on LSMO/STO interfaces [22]. Remarkably, a clear dichroic signal is also observed at the Ti edge demonstrating the ferromagnetic character of STO, although bulk STO is a diamagnetic band insulator.…”
supporting
confidence: 78%
“…One possible origin for the reduced TMR is the reduction of ferromagnetic ordering at the interface between the manganite and the STO. These interfacial effects have been suggested to be dominant as the LSMO layer thickness decreases, causing the magnetization and T c to degrade and the resistivity to increase, ultimately resulting in films that are insulating at all temperatures when the layer thickness decreases below a reported critical value of 7-13 unit cells (4)(5)(6)(7)(8)(9)(10)(11). This critical thickness for sustaining conductivity below T c is attributed to an inherent "dead layer" at the interface between LSMO and STO (12)(13)(14).…”
mentioning
confidence: 99%
“…In this respect experimental investigations by surface sensitive x-ray magnetic scattering of layered manganite single crystals 22 and of perovskite manganite thin films 23 have shown that the average in-plane FM ordering of the surface is significantly suppressed over a length scale of about 4 unit cells (u.c.) from the surface, even at low temperature.…”
Section: Introductionmentioning
confidence: 99%